Ramadan fasting in insulin-treated patients is associated with potentially unfavourable changes in glucose metrics: A flash glucose monitoring (FGM) study. (February 2021) - Saadane, Ilham; Ali, Tomader; El-Laboudi, Ahmed; Lessan, Nader
Abstract: Aim(s): Ramadan fasting (RF) can represent various challenges to glycaemic control especially in insulin-treated patients with diabetes. We aimed to assess the effect of RF on several glucose metrics using flash glucose monitoring (FGM). Methods: Complete FGM data for 29–30 days before, during and after Ramadan were available for 40 patients with type 1 (n = 13) and type 2 diabetes (n = 27) on insulin (with or without oral hypoglycaemic) treatment. Indicators of mean glucose, glucose variability (GV) and time in different glycaemic ranges were analysed. Results: RF was associated with increase in time in hyperglycaemia (38.5 ± 18.2 vs 48.7 ± 20.7%; P < 0.001) and decrease in time in hypoglycaemia (3.2 ± 2.8 vs 2.1 ± 2.1%; P = 0.003), and time in target range (56.3 ± 17.2 vs 47.9 ± 19.7%, P < 0.001). There were no significant differences in markers of GV with RF; however, RF was associated with a significant reduction in GV during the day but not night time with an increase in the ensuing non-fasting period. Conclusions: In insulin-treated patients, RF is associated with an increase in time in hyperglycaemia, a reduced time in target range and nocturnal increase in GV, indicating a need for more refined management algorithms.